FRI0407 Dipeptidyl-peptidase-4 (DPP4) is a potential new molecular target for treatment of fibrosis. (12th June 2018) - Soare, A.M.; Györfy, H.; Matei, A.; Dees, C.; Zhang, Y.; Wohlfahrt, T.; Chen, C.-W.; Ramming, A.; Schett, G.; Distler, J.
Abstract : Background: Dipeptidyl-peptidase-4 (DPP4) plays a role in tissue scaring and its inhibition leads to reduced scar formation. Its function in tissue fibrosis, however, is unknown. Objectives: The aim of the study was to investigate the expression of DPP4 in fibrotic tissue of systemic sclerosis (SSc) patients, to characterise DPP4 positive cells, to study the mechanism of action of DPP4 in fibroblasts and to evaluate the antifibrotic effect of pharmacological and genetically inhibition of DPP4 in different preclinical models of SSc. Methods: Expression of DPP4 in human and murine skin was analysed. Mouse fibroblasts were isolated and DPP4 positive cells properties were assessed. Pulmonary fibrosis was induced by bleomycin in DPP4 knockout (KO) mice and wildtype littermates. Fibrosis of the lungs was additionally evaluated by computer tomography scans (CT). Two oral DPP4 inhibitors were tested in two concentrations in bleomycin-induced skin fibrosis and in sclerodermatous chronic graft-versus-host disease (scl-cGvHD) model. Antiinflammatory effects of DPP4 inhibition were assessed by CD45 staining of fibrotic and non-fibrotic mouse tissue upon DPP4 inhibition. Moreover, chimeric mice were generated by transplanting bone marrow from DPP4-KO mice in WT-littermates (DPP4→WT) and vice versa (WT→DPP4) and fibrosis was by intratracheal injections of bleomycin. Results: DPP4 positive fibroblasts were increased in fibrotic skin of SSc patients and also in murine models of fibrosis. DPP4 expression is induced by TGF-β in an Erk-dependent manner. DPP4-positive fibroblasts strongly express stress fibres after TGF-β stimulation and released increased amounts of collagen. Mechanistically, inhibition of DPP4 selectively interferes with the TGF-β induced activation of ERK signalling, but does not inhibit TGF-β induced SMAD signalling, or other non-canonical TGF-β pathways involving Fra2, c-Jun, p38, Akt or STAT3. Furthermore, pharmacological inhibition of DPP4 reduced the release of collagen and the expression of myofibroblast markers. DPP4-KO mice are less sensitive to bleomycin-induced pulmonary fibrosis as shown by milder changes on CT, reduced Ashcroft scores and reduced hydroxyproline content. DPP4-KO mice also show reduced skin fibrosis upon bleomycin challenge. Moreover, treatment with DPP4 inhibitors demonstrated potent antifibrotic effects in bleomycin-induced skin fibrosis and experimental scl-cGvHD mouse model. Treatment with DDP4 inhibitors also reduced leukocyte infiltrations into the skin. The extent of pulmonary fibrosis of DPP4→WT was comparable to that of WT→WT control mice. Fibrosis was strongly ameliorated in WT→DPP4 mice and results were comparable to that of DPP4→DPP4 mice, characterising resident cells such as fibroblasts as major target cells for the antifibrotic effects of DPP4 inhibitors. Conclusions: DPP4 characterises an activated subpopulation of fibroblasts in SSc. Moreover, inhibitors of DPP4 show a significant anti-fibrotic effect in several mouse models of SSc in well tolerated doses. These results may have direct translational implications as DPP4 inhibitors are already in clinical use for diabetes. Acknowledgements: AS received a scientific training bursary from the European League Against Rheumatism. Disclosure of Interest: None declared